The Use Of Euphemism Found In Celebrity Newsnpublished In The CNN Website - Rivo Yulian Krisdawati; Agustinus Hary Setyawan (Jurnal Dunia Pendidikan, 2023)
One of the language phenomena that exists in society to keep the relationship in good harmony is euphemism. This research intends to describe euphemism forms and functions found in Celebrity News published in the CNN (edition.cnn.com) website. This research is descriptive qualitative based on the phenomena of euphemism in written language. Data of this research are words, phrases, and sentences that contain euphemistic expressions found in Celebrity News during March 2023. The research results show that there are four forms and four functions of euphemism. The form of euphemism that is mostly found is semantic change, especially metaphorical transfer. The researcher also found various functions of euphemism. The function of euphemism that is mostly found is avoiding taboo.